ANGIOTENSIN II AND MYOCARDIAL INFARCTION - O. P. Shevchenko; А. О. Shevchenko (Столичная издательская компания, 2016)
The role of angiotensin II in pathogenesis of cardiovascular diseases is discussed. Angiotensin II participates in development of acute myocardial infarction (MI) in patients with atherosclerosis. It contributes to inflammation of vessel intimae, oxidative stress, cells apoptosis, matrix remodeling, has pro-thrombosis action, promotes MI expansion and post-MI remodeling. Angiotensin converting enzyme (ACE) inhibitors reduce mortality and improve prognosis of patients with acute MI. In patients with ischemic heart disease including patients after MI ACE inhibitors reduce mortality, risk of repeated MI as well as improve quality of life.